Silicon improves the redox homeostasis to alleviate glyphosate toxicity in tomato plants—are nanomaterials relevant? - Soares, Cristiano (2021)
Given the widespread use of glyphosate (GLY), this agrochemical is becoming a source of contamination in agricultural soils, affecting non-target plants. Therefore, sustainable strategies to increase crop tolerance to GLY are needed. From this perspective and recalling silicon (Si)’s role in alleviating different abiotic stresses, the main goal of this study was to assess if the foliar application of Si, either as bulk or nano forms, is capable of enhancing Solanum lycopersicum L. tolerance to GLY (10 mg kg−1). After 28 day(s), GLY-treated plants exhibited growth-related disorders in both shoots and roots, accompanied by an overproduction of superoxide anion (O2•−) and malondialdehyde (MDA) in shoots. Although plants solely exposed to GLY have activated non-enzymatic antioxidant mechanisms (proline, ascorbate and glutathione), a generalized inhibition of the antioxidant enzymes was found, suggesting the occurrence of great redox disturbances. In response to Si or nano-SiO2 co-application, most of GLY phytotoxic effects on growth were prevented, accompanied with a better ROS removal, especially by an upregulation of the main antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX). Overall, results pointed towards the potential of both sources of Si to reduce GLY-induced oxidative stress, without major differences between their efficacy.